Neurological examination is changing - A. Jasionis; R. Mameniškienė (Neurologijos seminarai)
Patient examination during the COVID-19 pandemic should be short and fruitful, physicians should avoid unnecessary actions of direct contact. In certain situations, remote consultations are preferred. This commentary proposes several modifications to the neurological exam to make it shorter and to avoid potential actions of higher epidemiological risk. Three situations are discussed: examination of the patient with COVID-19, urgent neurological examination, and teleneurological examination.